Artificial Intelligence Governance and Regulation: A Roadmap to Developing Legal Policies for Artificial Intelligence Deployment - Trisnawati (Universitas Airlangga, 2024)
Abstract The rapid advancement of artificial intelligence (AI) presents substantial challenges for global regulation and governance. This study explores various approaches adopted by countries and industries in formulating legal policies that promote the responsible and innovative use of AI. It examines regulatory frameworks in the European Union, the United States, and China, alongside the deployment of AI in the automotive and healthcare sectors. Empirical evidence suggests that stringent regulations, such as those in the European Union, enhance legal clarity and foster public trust but impose higher compliance costs and hinder innovation. Conversely, the United States' more lenient approach promotes innovation but leads to legal ambiguity. Key global challenges, including standards harmonization, algorithm transparency, and accountability, remain critical issues for stakeholders. The study concludes by emphasizing the need for an equilibrium between innovation and regulation, achieved through international collaboration to establish robust, secure, and sustainable AI governance frameworks. Keywords: Artificial Intelligence, AI policy, AI governance, AI regulation Abstrak Pesatnya perkembangan kecerdasan buatan (AI) membawa tantangan yang signifikan dalam hal regulasi dan tata kelola global. Artikel ini bertujuan untuk memeriksa pendekatan berbagai negara dan industri dalam mengembangkan kebijakan hukum yang mendukung penerapan AI yang bertanggung jawab dan inovatif. Studi ini menyoroti peraturan di Uni Eropa, Amerika Serikat, dan Cina, serta penerapan AI di sektor otomotif dan perawatan kesehatan. Data empiris menunjukkan bahwa meskipun peraturan yang ketat, seperti di Uni Eropa, memberikan kejelasan hukum dan meningkatkan kepercayaan publik, itu juga menambah beban biaya dan memperlambat inovasi. Di sisi lain, pendekatan yang lebih longgar di Amerika Serikat mendorong inovasi tetapi menciptakan ketidakpastian hukum. Tantangan global dalam harmonisasi standar, transparansi algoritma, dan akuntabilitas adalah masalah utama yang harus ditangani oleh para pemangku kepentingan. Artikel ini menyimpulkan bahwa keseimbangan antara inovasi dan regulasi diperlukan melalui kolaborasi internasional untuk menciptakan tata kelola AI yang tangguh, aman, dan berkelanjutan. Kata kunci: Kecerdasan Buatan, kebijakan AI, Tata Kelola AI, dan Regulasi AI.